TEOLOGI BIBLIKA KONTEKSTUAL: MANFAAT STUDI BIBLIKA KONSTEKSTUAL DALAM KEHIDUPAN IMAN KRISTIANI DI ERA DISTRUPTIF - Deni Baso’; Agung Jaya (Adiba Aisha Amira, 2022)
Biblical theology represents one of the most influential means that evangelicals have used to construct theology over the last few centuries. As we continue to study this approach to the Bible, we will find that it complements the more traditional approaches to theology, and also draws attention to so many insights that have often been overlooked in the past. A well-formulated biblical theology will help us to explore God's word more thoroughly and build a theology that is faithful to the Bible and builds up the church. In simple terms, biblical theology is a Christian response to a prominent intellectual movement in modern times, which is often called modern historicism. In general, modern historicism is the belief that history holds the key to understanding ourselves and the world around us. According to this view, an adequate understanding of things can only be obtained by considering their place in history. The current era of disruption marked by the birth of sharing innovations and new technologies cannot be avoided by all people, organizations and churches. The era of disruption will affect Christian faith, so the attitudes, policies and culture taken by believers of Christian faith on the effects of this disruptive era will determine whether their Christian faith will continue to grow steadily or will die completely. The disruptive era is an era where changes occur in such an unexpected, fundamental way that covers almost all aspects of life.